Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1093/pasj/psv138
|View full text |Cite
|
Sign up to set email alerts
|

V1006 Cygni: Dwarf nova showing three types of outbursts and simulating some features of the WZ Sge-type behavior

Abstract: We observed the 2015 July-August long outburst of V1006 Cyg and established this object to be an SU UMa-type dwarf nova in the period gap. Our observations have confirmed that V1006 Cyg is the second established object showing three types of outbursts (normal, long normal and superoutbursts) after TU Men. We have succeeded in recording the growing stage of superhumps (stage A superhumps) and obtained a mass ratio of 0.26-0.33, which is close to the stability limit of tidal instability. This identification of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
(41 reference statements)
4
5
0
Order By: Relevance
“…During the short-term quiescence between the rebrightening and the start of the first normal outburst the mean period of positive superhumps was P 2 = 0 d .10406(17). These periods are in agreement with periods found by Kato et al (2016) superhumps evolution during JD 2457219 -2457240. A periodogram in quiescence after the first normal outburst points to the most significant peaks P 4 = 0 d .107594(85) and P 5 = 0 d .097142(74) that are not independent but are the day-aliased.…”
Section: Superoutburstsupporting
confidence: 90%
See 4 more Smart Citations
“…During the short-term quiescence between the rebrightening and the start of the first normal outburst the mean period of positive superhumps was P 2 = 0 d .10406(17). These periods are in agreement with periods found by Kato et al (2016) superhumps evolution during JD 2457219 -2457240. A periodogram in quiescence after the first normal outburst points to the most significant peaks P 4 = 0 d .107594(85) and P 5 = 0 d .097142(74) that are not independent but are the day-aliased.…”
Section: Superoutburstsupporting
confidence: 90%
“…Our data are in good agreement with an empirical relation between ǫ + , ǫ − and the orbital period (Hellier, 2001). Moreover, we found that the ratio ǫ − /ǫ + = −0.037 corresponds to the mass ratio q ∼ 0.30 − 0.32 according to the Wood's et al (2009) model, that coincides with an independent estimate of Kato et al (2016), q ∼ 0.26 − 0.33. So we can conclude that our identification of the period 0 d .09714 as the period of negative superhumps is correct.…”
Section: Superoutburstsupporting
confidence: 84%
See 3 more Smart Citations